Quantification and prescription: what is the situation concerning room for manoeuvre enjoyed by social workers and users? - Artois, Pierre (Acciones e Investigaciones Sociales, 2021)
The implementation of social policies has led to the principle of making evaluation a standard for organizing the vocational integration sector. Evaluating social policies is currently all but limited exclusively to analyzing quantitative criteria determined by subsidiary claims dependent on political will. In this article we propose a critical and reflective approach based on a case study, seeking to answer a three-pronged question, namely: what are the effects on how work is organized, on the recipients of social measures, and on the workers themselves?